A183 SOFOSBUVIR-BASED ALL-ORAL REGIMENS FOR PATIENTS WITH CHRONIC HEPATITIS C GENOTYPE 3 INFECTION: INTEGRATED ANALYSIS OF FIVE CLINICAL STUDIES. (1st March 2018) - Foster, G R; Zeuzem, S; Gane, E J; Stedman, C; Feld, J; Mangia, A; Agarwal, K; Swain, M; Mir, H; Troke, P; Llewellyn, J; Natha, M; et al.
Abstract: Aims: Hepatitis C virus (HCV) genotype 3 (GT3) infection represents the second most common genotype worldwide and is currently considered the most difficult genotype to treat. AASLD and EASL guidelines recommend sofosbuvir (SOF) based regimens for the treatment of patients with HCV GT3. This analysis evaluated the efficacy and safety of various 12-week SOF-based all-oral regimens for HCV GT3 from Phase 2 and 3 clinical studies Methods: In the phase 2 ELECTRON-2 study, 26 treatment-naïve (TN) and 50 treatment-experienced (TE) HCV GT3 patients received 12 weeks of ledipasvir 90 mg (LDV)/SOF 400 mg daily + weight-based ribavirin (RBV) 1000 or 1200 mg divided twice daily. In the phase 2 CANADA study, 111 TN HCV GT3 patients received 12 weeks of LDV/SOF+RBV. In the phase 3 ALLY-3 study, 101 TN and 51 TE HCV GT3 patients received 12 weeks of SOF 400mg + daclatasvir 60 mg (DCV) daily. In the phase 3 ALLY-3+ study, 6 TN and 18 TE HCV GT3 patients received 12 weeks of SOF+DCV+RBV. In the phase 3 ASTRAL-3 study, 206 TN and 71 TE HCV GT3 patients received 12 weeks of SOF 400 mg/velpatasvir 100 mg (VEL) daily, compared to 275 patients who received 24 weeks of SOF+RBV. Patients with compensated cirrhosis were allowed to enroll in all studies. Results: 640 patients with HCV GT3 were enrolled in 5 clinical studies in North America, Europe, Australia, and New Zealand. Overall in all studies, the patients were male (62%), white (86%), and had IL28B non-CC genotype (61%). 190 patients (30%) were TE and 197 patients (31%) had compensated cirrhosis. Treatment responses will be reported. Therapy was well-tolerated with no patients discontinuing all treatment due to an adverse event. Conclusions: SOF/VEL for 12 weeks achieved the highest SVR12 and lowest relapse rates seen among the 5 studies, including in compensated cirrhotic patients, and was superior to 24 weeks of SOF+RBV. It offers a fixed-duration, IFN- and RBV-free, well-tolerated, and highly effective therapy, even for difficult-to-treat GT3 patients. Funding Agencies: Gilead Sciences Inc.